Larval morphology and identification of Rhyacophila meyeri McLachlan 1879 (Trichoptera: Rhyacophilidae) - Waringer, Johann; Vitecek, Simon; Graf, Wolfram (Zootaxa, 2016)
This paper describes the previously unknown larva of Rhyacophila meyeri McLachlan 1879. Information on the morphology of the 5th larval instar is given, and the most important diagnostic features are illustrated. In the context of existing identification keys the larva of R. meyeri keys together with R. stigmatica (Kolenati 1859). The species pair can be separated by differences in the setation pattern at the anterior pronotal border and maximum head width.With respect to zoogeography, Rhyacophila meyeri is reported from Switzerland and northern Italy whereas R. stigmatica is restricted to the Austrian, German and Swiss Alps and northern Slovenia (Cianficconi 2002; Graf et al. 2008; Lubini-Ferlin & Vicentini 2005; Malicky 2009; Robert 2004).